2008
DOI: 10.1021/bp060379e
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Alginate Bead Immobilization of Cells Containing Tyrosine Ammonia Lyase Activity for Use in the Production of p-Hydroxycinnamic Acid

Abstract: An Escherichia coli catalyst with tyrosine ammonia lyase activity (TAL) has been stabilized for repeated use in batch conversions of high tyrosine solids to p-hydroxycinnamic acid (pHCA). The TAL biocatalyst was stabilized by controlling the reaction pH to 9.8 +/- 0.1 and immobilizing the cells within a calcium alginate matrix that was cross-linked with glutaraldehyde and polyethyleneimine (GA/PEI). We found a GA range where the bead-encapsulated TAL was not inactivated, and the resulting cross-linking provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, some PAL enzymes can accept tyrosine as an alternative substrate (PAL/TAL) and directly form p -coumaric acid from tyrosine without the intermediacy of trans -cinnamic acid (Figure 1) [16]. Also, there are some aromatic amino acid ammonia-lyase homolog enzymes specific for tyrosine deamination (TAL) (Figure 1) [17], so introducing a heterologous PAL/TAL or TAL, p -coumaric acid could be produced via the tyrosine route in recombinant cells such as Escherichia coli [18,19,20], Saccharomyces cerevisiae [21], Streptomyces lividans [22] and Pseudomonas putida [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, some PAL enzymes can accept tyrosine as an alternative substrate (PAL/TAL) and directly form p -coumaric acid from tyrosine without the intermediacy of trans -cinnamic acid (Figure 1) [16]. Also, there are some aromatic amino acid ammonia-lyase homolog enzymes specific for tyrosine deamination (TAL) (Figure 1) [17], so introducing a heterologous PAL/TAL or TAL, p -coumaric acid could be produced via the tyrosine route in recombinant cells such as Escherichia coli [18,19,20], Saccharomyces cerevisiae [21], Streptomyces lividans [22] and Pseudomonas putida [23].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme P450 monooxygenase cinnamate 4-hydroxylase (C4H) can further oxidize the cinnamic acid yielding the p-coumaric acid (Rasmussen et al, 1999;Achnine et al, 2004). The heterologous expression of TAL and PAL/TAL encoding genes allowed the p-coumaric acid production in E. coli, S. cerevisiae, Streptomyces lividans and P. putida (Table 1; Nijkamp et al, 2007;Trotman et al, 2007;Vannelli et al, 2007;Kawai et al, 2013;Rodriguez et al, 2015;Vargas-Tah and Gosset, 2015). However, due to their low activity, first studies reported its production from culture medium supplemented with L-Phe or L-Tyr (Ro and Douglas, 2004;Hwang et al, 2003;Watts et al, 2004;Jendresen et al, 2015;Mao et al, 2017).…”
Section: Strategies For Production Of Aromatic Compoundsmentioning
confidence: 99%
“…TAL plays a critical role in synthesizing the chromophore of photoactive yellow protein in bacteria and for caffeic acid biosynthesis in actinomycetes (Kyndt et al, 2002(Kyndt et al, , 2003Berner et al, 2006). Multiple research groups have used TAL for metabolic engineering of flavonoid and resveratrol biosynthesis pathways that require p-coumaric acid 4 as a precursor molecule (Watts et al, 2004;Jiang et al, 2005;Zhang et al, 2006;Qi et al, 2007;Trotman et al, 2007). Because TAL forms pcoumaric 4 acid directly from L-tyrosine 3, its use in heterologous expression systems circumvents the need to express both PAL and 4-coumaric acid hydroxylase, a membranebound cytochrome P450 enzyme, for conversion of L-phenylalanine 1 to p-coumaric acid 4.…”
mentioning
confidence: 99%